2002
DOI: 10.1046/j.1365-3040.2002.00796.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant water relations at elevated CO2– implications for water‐limited environments

Abstract: and drought are needed, as are whole-plant investigations that emphasize the integration of processes throughout the soil-plantatmosphere continuum. We suggest that the hydraulic principles that govern water transport provide an integrating framework that would allow CO 2 -induced changes in stomatal conductance, leaf water potential, root growth and other processes to be uniquely evaluated within the context of whole-plant hydraulic conductance and water transport efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
278
2
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(317 citation statements)
references
References 97 publications
22
278
2
3
Order By: Relevance
“…Vegetation also exerts controls on production of CO 2 through root respiration in the soil and through complex mycorrhizal associations that can mediate the response of soil CO 2 production to rain pulse events (Vargas et al, 2010). Finally, vegetation also elicits feedbacks on the abiotic aspects of a system, including the soil moisture and soil temperature regimes, further impacting biogeochemical cycling (Wullschleger et al, 2002;Metcalfe et al, 2011;Vesterdal et al, 2012).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…Vegetation also exerts controls on production of CO 2 through root respiration in the soil and through complex mycorrhizal associations that can mediate the response of soil CO 2 production to rain pulse events (Vargas et al, 2010). Finally, vegetation also elicits feedbacks on the abiotic aspects of a system, including the soil moisture and soil temperature regimes, further impacting biogeochemical cycling (Wullschleger et al, 2002;Metcalfe et al, 2011;Vesterdal et al, 2012).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…Climate change is predicted to shape new hydroclimatic regimes in many regions of the 47 world (Ramanathan et water-limited regions (Wullschleger et al, 2002), such as Australia (Eamus et al, 2006). 57…”
Section: Introduction 46mentioning
confidence: 99%
“…However, only relatively few investigations have considered the direct consequences of soil water deficits imposed on plants that are exposed to elevated CO 2 atmospheres (Serraj et al 1999). In studies concerned with the interactive effects of elevated CO 2 and water stress, some found that elevated CO 2 significantly increased plant growth (Kimball et al 1995;Centritto et al 1999;Serraj et al 1999;Ottman et al 2001;Wall et al 2001), possibly because plants growing in elevated CO 2 improved water relations under drought stress and were able to withstand the drought stress better (Grant et al 1999;Wall 2001;Wall et al 2001;Wullschleger et al 2002). However, there were also studies finding no positive effects of elevated CO 2 on plant growth under drought-stressed conditions (Mo et al 1992;Ward et al 1999;Derner et al 2003).…”
Section: Introductionmentioning
confidence: 99%